2017
DOI: 10.1111/liv.13405
|View full text |Cite
|
Sign up to set email alerts
|

Role of HLADP and HLADQ on the clearance of hepatitis B virus and the risk of chronic infection in a multiethnic population

Abstract: This is the first study addressing the associations between the HLA-DP and HLA-DQ loci and the protection against chronic HBV and viral clearance in a multiethnic South American population. The uneven distribution of HLA-DP and HLA-DQ supports the HBV epidemiological differences observed in these two regions of Argentina with dissimilar ancestry genetic background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…The rs3077‐T allele is the minor allele among individuals with Asian ancestry but is the major allele among those with European ancestry, according to the data of the HapMap project and from the pilot studies of the 1000 Genomes project (https://www.ncbi.nlm.nih.gov/projects/SNP/snp_ref.cgi?rs=3077, assessed on 28 May 2017). This is also in accordance with the findings of numerous studies, including a healthy control group in Asian and in Caucasian populations, and with the allele frequency observed in our HC group (84.3% for the T allele). Our study confirms for the first time the protective role of the rs3077‐T allele, independently of the population origin.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The rs3077‐T allele is the minor allele among individuals with Asian ancestry but is the major allele among those with European ancestry, according to the data of the HapMap project and from the pilot studies of the 1000 Genomes project (https://www.ncbi.nlm.nih.gov/projects/SNP/snp_ref.cgi?rs=3077, assessed on 28 May 2017). This is also in accordance with the findings of numerous studies, including a healthy control group in Asian and in Caucasian populations, and with the allele frequency observed in our HC group (84.3% for the T allele). Our study confirms for the first time the protective role of the rs3077‐T allele, independently of the population origin.…”
Section: Discussionsupporting
confidence: 93%
“…Apart from HBV persistence, we also intended to investigate whether the HLA SNPs are associated with different stages of chronic HBV infection. We found no association with inactive carrier state, HBeAg state or cirrhosis, which is in accordance with other studies on Caucasians, Asians or mixed populations, although in our study the number of cirrhosis cases was quite small. However, a Chinese study has suggested that rs9277534 might be associated with the progression from asymptomatic HBV carriers to HBV‐related cirrhosis .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations